Pediatric Epilepsy Management: Special Considerations - Nickels, Katherine; Joshi, Charuta (Seminars in Neurology, 2025)
While pediatric epilepsy shares some features with adult epilepsy, the growing and developing brain during childhood is associated with differences in epilepsy etiologies, syndromes, comorbidities, management, and outcomes. We must also consider the long-term effects of epilepsy and treatments. This section highlights unique considerations for pediatric epilepsy. These include pediatric onset electroclinical syndromes that commonly resolve prior to adulthood, treatment duration of self-limited pediatric epilepsy syndromes, pediatric-onset epilepsy with etiology-specific treatment, and therapies used more commonly in the pediatric population. In addition, pediatric-onset epilepsy is associated with a higher risk for developmental, psychiatric, and behavioral comorbidities in a bidirectional fashion. Family dynamics are affected by a child with epilepsy, and transitioning to the adult clinic is a particular challenge for this population. Finally, there are special issues that occur in pediatric epilepsy, including the lack of pediatric FDA approvals for newly available therapies and the need for sedation for investigations.
Keywords: epilepsy; pediatric; comorbidities; electroclinical syndromes; antiseizure medications